The anthology and the rise of the novel : from Richardson to George Eliot - Price, Leah. (Cambridge [England] ; New York : Cambridge University Press, 2000)
"The Anthology and the Rise of the Novel brings together two traditionally antagonistic fields, book history and narrative theory, to challenge established theories of "the rise of the novel." Leah Price shows that far from leveling class or gender distinctions, as has long been claimed, the novel has consistently located them within its own audience. Shedding new light on Richardson and Radcliffe, Scott and George Eliot, this book asks why the epistolary novel disappeared, how the book review emerged, why eighteenth-century abridgers marketed their books to women while Victorian publishers repackaged them for men, and how editors' reproduction of old texts has shaped authors' production of new ones. This book will change the way we think not just about the history of reading, but about the genealogy of the canon wars, the future of intellectual property, and the role that anthologies play in our own classrooms."--Jacket
Richardson's economies of scale -- Cultures of the commonplace -- Knox's Scissor-Doings -- George Elliot and the production of consumers.
Includes bibliographical references (pages 198-218) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Richardson, Samuel, -- 1689-1761 -- Criticism and interpretation; Eliot, George, -- 1819-1880 -- Criticism and interpretation; Richardson, Samuel, -- 1689-1761 -- Critique et interprétation.; Eliot, George, -- 1819-1880 -- Critique et interprétation.; Eliot, George, -- 1819-1880; Richardson, Samuel, -- 1689-1761; Richardson, Samuel, -- 1689-1761.; Eliot, George, -- 1819-1880.; Eliot, George; Richardson, Samuel; English fiction -- 18th century -- History and criticism; English fiction -- 19th century -- History and criticism; Anthologies -- Editing -- History; Literary form; Anthologies -- History and criticism; Roman anglais -- 18e siècle -- Histoire et critique; Roman anglais -- 19e siècle -- Histoire et critique; Anthologies -- Histoire et critique; Genres littéraires.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Anthologies -- Editing; English fiction; Literary form; Anthologie; Roman; Bloemlezingen; Ontstaansgeschiedenis; Romans; Engels; Roman -- englischer -- Anthologie -- Geschichte 18. Jh; Anthologie -- Roman -- englischer -- Geschichte 18. Jh; Lesen -- (Leser) -- Grossbritannien -- Geschichte 18. Jh; Lesen -- (Leser) -- Grossbritannien -- Geschichte 19. Jh; Anthologie -- Roman -- englischer -- Geschichte 19. Jh; Roman -- englischer -- Anthologie -- Geschichte 19. Jh; Kanon -- (Literar.) -- Grossbritannien -- Geschichte 18. Jh; Kanon -- (Literar.) -- Grossbritannien -- Geschichte 19. Jh; Novels -- England -- 18th century; Novels -- England -- 19th century; Book production -- History -- 18th-19th century; Anthologies; Book market -- 18th-19th century; Englisch; 1700-1899; Criticism, interpretation, etc; History